Effect of Exhaustive Exercise on the Swimming Capability and Metabolism of Juvenile Siberian Sturgeon. Issue 3 (22nd April 2015) - Cai, L.; Johnson, D.; Mandal, P.; Gan, M.; Yuan, X.; Tu, Z.; Huang, Y.
Abstract: This study investigated the effect of exhaustive exercise on the swimming performance of Siberian Sturgeon Acipenser baeri and on the time required for recovery. Critical swimming speed ( U crit ), maximum metabolic rate (MMR), speed coefficient ( c ), and excess postexercise oxygen consumption (EPOC) were measured on three groups of juvenile sturgeon by stepped velocity tests at 20°C in a fish respirometer. After a recovery period of 1 h (group 1), 1 d (group 2), or 1 week (group 3), the four parameters were determined a second time and the results compared. The U crit of the sturgeon was 3.26 ± 0.11 body lengths per second (mean ± SE). After a 1 h recovery period, U crit was 78% of its initial value and complete recovery required slightly more than 1 d. Recovery of MMR followed the same pattern. The speed exponent ( c ) was approximately 1.0, indicating that the Siberian Sturgeon is an efficient swimmer; swimming efficiency decreased after exhaustive exercise and the effect appeared to last for at least 1 week. Exhaustive exercise strongly hindered anaerobic swimming in Siberian Sturgeon for more than an hour.